Effector-triggered post-translational modifications and their role in suppression of plant immunity - Howden, Andrew J.; Huitema, Edgar (Frontiers in Plant Science, 2012)
Plant-pathogen interactions feature complex signalling exchanges between host and microbes that ultimately determine association outcomes. Plants deploy Pattern Recognition Receptors (PRRs) to perceive Pathogen Associated Molecular Patterns (PAMPs), mount Pattern Triggered Immunity (PTI) and fend off potential pathogens. In recent years an increasing number of defence signalling components have been identified along with a mechanistic understanding of their regulation during immune responses. Post-translational modifications (PTMs) are now thought to play a crucial role in regulating defence signalling. In a bid to suppress PTI and infect their host, pathogens have evolved large repertoires of effectors that trigger susceptibility and allow colonization of host tissues. While great progress has been made in elucidating defence signalling networks in plants and the activities of effectors in immune suppression, a critical gap exists in our understanding of effector mechanism-of-action. Given the importance of PTMs in the regulation of defence signalling, we will explore the question: how do effectors modify the post-translational status of host proteins and thus interfere with host processes required for immunity? We will consider how emerging proteomics based experimental strategies may help us answer this important question and ultimately open the pathogens’ effector black box.